Transfer of POCUS Skills of Anesthesia Trainees from the Simulation Laboratory to Clinical Practice: A Follow-Up Pilot Evaluation After ABC US Protocol Training - Robert Simon; Cristina Petrișor; Constantin Bodolea; Oana Antal; Marta Băncișor; Orlanda Moldovan; Ion Cosmin Puia (Diagnostics)
Background/objectives: Point-of-care ultrasound (POCUS) in the intensive care unit (ICU) has gained much attention in the last few years as an alternative to the classic ways of assessing and diagnosing life-threatening conditions in critical patients. During the COVID-19 pandemic, we proposed a POCUS protocol based on the airway, breathing, and circulation (ABC) approach to quickly evaluate and diagnose life-threatening diseases in critical patients with acute respiratory failure and shock, and later, we used it as a curriculum to teach POCUS to anesthesia and intensive care trainees. Methods: We developed an evaluation protocol where evaluators with experience in POCUS in critically ill patients had to assess the trainee’s ultrasound scan; this was based on the ABC protocol taught in the simulation laboratory and applied in a clinical setting at the bedside. Results: Statistically significant differences were observed in some categories evaluated regarding independence and diagnosis. Conclusion: Initial POCUS simulation-based training using an ABC POCUS protocol (that demonstrated good results in the simulation laboratory) is useful when transferring US skills to the bedside and is applicable in daily clinical practice with good results in terms of operator independence.